DEVELOPMENT OF COMMUNICATIVE COMPETENCE IN CHILDREN WITH INSUFFICIENT LANGUAGE DEVELOPMENT IN A PRE-SCHOOL EDUCATIONAL INSTITUTION - Kanča, Ilze; Usca, Svetlana (Education Reform: Education Content Research and Implementation Problems, 2022)
Communicative competence in a pre-school education institution allows children to get to know each other and gives them the opportunity to learn about things and events that are happening around them. Communicative competence includes the linguistic, discourse, pragmatic, strategic and socio-cultural elements of language. Educators need to be able to find appropriate methods to develop communicative competence. The aim of the paper is to study theoretically how to promote the development of communicative competence in children with insufficient language development in a pre-school.Research method: analysis of scientific literature.The paper concludes that research is needed on the impact of the use of drama as a method on the development of communicative competence in pre-school children with insufficient language development.